2021
DOI: 10.1590/s1517-707620210001.1233
|View full text |Cite
|
Sign up to set email alerts
|

Ti-25Nb-25Ta alloy treated by plasma electrolytic oxidation in phosphoric acid for implant applications

Abstract: Among titanium alloys with non-toxic elements, the Ti-25Nb-25Ta alloy has good elastic behavior for applications in osseous implants, biocompatibility, and excellent corrosion resistance. The present study aimed to better the biocompatibility characteristics of Ti-25Nb-25Ta alloy modifying its surface through Plasma Electrolytic Oxidation (PEO) treatment. The formed oxide coating is amorphous and composed of two distinct porous formations: smaller hole-shaped pores and larger volcano-like pores. The regions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Hence, there is an important need for environmentally friendly cleaning processes. Besides well-studied processes such as plasma nitriding [2], nitrocarburizing [3], and plasma electrolytic oxidation [4], plasma technology has also been studied for cleaning purposes and has shown great potential for development. Some authors worked with oil removal from metal surfaces using plasma [5][6][7][8], and other authors [9,10] showed the importance of plasma cleaning in some industry fields, especially aeronautics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an important need for environmentally friendly cleaning processes. Besides well-studied processes such as plasma nitriding [2], nitrocarburizing [3], and plasma electrolytic oxidation [4], plasma technology has also been studied for cleaning purposes and has shown great potential for development. Some authors worked with oil removal from metal surfaces using plasma [5][6][7][8], and other authors [9,10] showed the importance of plasma cleaning in some industry fields, especially aeronautics.…”
Section: Introductionmentioning
confidence: 99%